Mapping QTL associated with Verticillium dahliae resistance in the cultivated strawberry (Fragaria × ananassa). (11th March 2015) - Antanaviciute, L; Šurbanovski, N; Harrison, N; McLeary, K J; Simpson, D W; Wilson, F; Sargent, D J; Harrison, R J
Abstract: A biparental cross of octoploid strawberry segregating for resistance to Verticillium dahliae, the causative agent of Verticillium wilt, was screened under field conditions for three seasons. Average wilt scores were significantly associated with multiple QTL, which were mostly significant across all years. Markers significantly associated with the traits were used to screen material with known wilt resistance and susceptibility phenotypes. A clear and statistically significant relationship was observed between resistant, tolerant and susceptible material and the total number of markers present in the different resistance classes. In field situations resistance QTL appear to behave in an additive manner. These markers are abundant in the cultivated strawberry germplasm indicating that, despite the large number of markers, clear genetic gain is possible through marker-assisted breeding. Abstract : Soft fruit: Getting to the root of strawberry wilt Field studies in strawberries have identified a number of genetic regions providing resistance to a debilitating wilt disease. Verticillium wilt is a soil-borne fungal pathogen that infects strawberries and many other crops through the roots, causing wilting and cell death. With only a single chemical treatment available, there is an urgent need to improve crops' resistance to the disease. Researchers led by Richard Harrison, of East Malling Research, UK, scored a large population of strawberries for resistance or susceptibility to Verticillium wilt. They found resistance was strongly correlated with multiple genetic marker regions. Wilt resistance appeared to be additive; that is, the more resistance-associated markers a plant had, the greater its resistance to wilt. Genetic markers are therefore a very useful tool for breeding strawberries resistant to this devastating disease.